LARGE AND SUPERLARGE VOLCANIC-ASSOCIATED MASSIVE SULFIDE DEPOSITS - Eremin N.I.; Dergachev A.L.; Pozdnyakova N.V.; Sergeeva N.E. (My University, 2004)
Large volcanic-associated massive sulfide deposits with reserves of Cu, Pb, or (and) Zn of more than 1, 0.6, and 2 Mt, respectively, are considered as large deposits. Superlarge (giant) deposits are those whose reserves exceed the minimum values for large deposits by five and more times. Most large deposits occur within the main massive sulfide provinces, which contain the major total reserves of ores and individual large and superlarge deposits. Maximum formation of large deposits occurred between 2750 and 2700 Ma and between 1900 and 1800 Ma, as well as during the Cambrian to the Early Ordovician and especially during the Devonian to the Early Carboniferous, the major epochs of massive sulfide ore formation in the Earth's history. Such deposits contain up to 50-80% of the metal reserves deposited during each of these epochs. Large primitive deposits are referred to the Archaean type; among Phanerozoic large deposits, most are classified as Kuroko and Uralian types, ordinary representatives of which have the most significant middle-scale reserves of ores and metals, while large Besshi-type deposits are rare. The occurrence and proximity of metal sources, structural factors, the duration of hydrothermal activity, and the volcanic regime are the most important factors in the formation of large reserves at deposits of this family. Large deposits can be referred to a group of ordinary deposits. They occur together with ordinary deposits of corresponding types. Their distribution patterns, ore composition, and ore formation mechanism are indistinguishable. For the formation of large deposits, no unique coincidences of factors in geologic history were required; therefore, large and superlarge deposits can be found on the basis of the same geological and prospecting models as ordinary deposits.